Thaddée Boulgarine et l'Abeille du Nord : Aux sources de la littérature de masse en Russie - Kirill Chekalov (Belphégor)
Faddey Boulgarin and the Northern Bee : the sources of mass literature in RussiaThe tradition of popular reading in Russia originated in the second half of the eighteenth century, when specimens of the first national novels – the works of Mikhail Chulkov, Matvej Komarov, Fedor Emin, etc. – were published along with numerous translations of foreign texts (mainly French). However, it is Faddey Bulgarin who should be looked upon as the real founding father of Russian popular literature. Bulgarin was the editor of the newspaper "The Northern bee", which enjoyed a great success in Russia, not only in the 1820s, but later as well. He was also the author of the first bestseller in the history of Russian prose, i.e. Ivan Vyjigin (1829).  Bulgarin  – the leading figure of the Russian mass reading – was harshly criticized by Pushkin, and later was negatively assessed by the Soviet literary criticism. His role in the literary evolution was revised only at the end of the twentieth century. In his novel Vyjigin Bulgarin, combines a variety of narrative traditions and creates a model of light reading, which pretends to reflect Russian national identity.